NORM Analysis of the Reservoir Sand Section in the Dorado Natural Gas Discovery Mannar Basin Offshore Sri Lanka - Ratnayake, R.M.T.S.; Gamage, S.S.N.; Senadhira, A.M.A.D.M.; Weerasinghe, D.A.; Waduge, V.A. (GEOL. SOC. INDIA, 2017)
Oil and Gas production always ties with drawing out of naturally-occurring radionuclides deposited beneath the earth, which are referred to as “NORM”. Understanding the prevailing background levels of these elements in the sub-surface reservoir rock formations will be beneficial to all stakeholders, more importantly to regulatory authorities of the country. The drill cutting samples from 5 m sampling intervals of natural gas reservoir sand section in the depth range 3025m to 3095m from deep water exploratory well “CLPL- Dorado 91 H/1z” drilled in the Mannar basin offshore Sri Lanka were tested in the laboratory using high-resolution Gamma-ray detectors. Test results revealed that the activity concentration of 40K, 210Pb,226Ra and 232Th levels and the calculated outdoor annual effective dose rate varies between considerably lower range when compared with the global standard limits. NORM concentration ranges of the sedimentary rocks within the tested section were recorded on the lower side, when the test results compared with the International Atomic Energy Agency published data on NORM concentration ranges of the sedimentary rocks found elsewhere in the world. Study results proved that there is no harmful public exposure of NORM by disposing these drill cuttings to environment or storing at any site location as it is. Also, it can be predicted that there will be very low level of NORM contaminations occur, if Dorado reservoir taken in to the production stage and well operations conducted with proper solid control mechanisms in future.